(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the vaccination status of children suffering from diphtheria, their clinical profile and outcome. Study Design: Descriptive cross-sectional study Place and Duration of Study: This study was conducted at the Department of Pediatrics, MTI/ Lady Reading Hospital Peshawar from July 2023 to December 2023. Methods: Data was collected after approval from Hospital ethical committee. Sample size was calculated through Open EPI and non-probability consecutive sampling technique was used. From arrival to departure, patients were followed. Results: A total of 67 children were included. Of them 40(59.7%) were male and 27(40.3%) were females. Mean age was 8.80±3.43 with range from 2 to 15 years. Out of them 39(58.2%) were unvaccinated, 20(29.9%) were partially vaccinated and 8(11.9%) were routinely vaccinated. 34(50.7%) had mild symptoms at arrival, 23 with bull neck and 10 with serious illness. In 45(67.1%) patients cardiac involvement was present ranging from sinus tachycardia to VT. 08(11.9%) had renal and 05(7.5%) had neurological involvement. 54(80.6%) received ADS and 13(20.4%) couldn’t. 12(17.9%) patients unfortunate outcome (died) and 55(82.1%) successfully recovered. Conclusion: This study shows that Diphtheria has resurged again and the most effective measures, vaccination, is very poor as majority (88%) of our patients are unvaccinated or partially vaccinated. Cardiac involvement is the major complication of diphtheria. A significant number of mortality occurs due to diphtheria and there is insufficiency of ADS for these patients.